Statement Of Cash Flows Reduces Financial Fraud With Documented Accounting Information - Haidar Omran Al-Jaber; Mondher Fakhfakh (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The research aimed to Emphasise the significance of the statement of cash flows developed by the International Accounting Standards Committee (IASC) and the International Accounting Standards Board (IASB) and Understand the concept of documented accounting information and Highlighting financial fraud and how to minimize it. The research problem was as follows from the fact that the financial statements, which do not contain the basic characteristics of accounting information, including reliability, will reduce the degree of reliance on them, which affects those lists prepared by financial institutions (banks) operating in Iraq that not taking into account the preparation of the cash flow statement will inevitably reduce the reliability of accounting information, resulting in misleading accounting outputs that will be a door to financial fraud in its various forms. Hence, the main research problem is the following question: Does enhancing the reliability of accounting information according to the preparation of the cash flow statement reduce financial fraud? The research reached many conclusions, the most important of which are International accounting standards can be said to be a written statement issued by an authorized body aimed at unifying and coordinating accounting treatments and policies to reach unified results for a set of financial transactions for ease of comparisons and understanding by the relevant parties. The statement of cash flows works to provide historical changes in financial institutions and others through and for a specific period of time and these flows are either operational, investment or financing for their various activities. The research reached many recommendations, the most important of which are: Emphasis on the different economic units to prepare a statement of cash flows because of the information it provides on historical changes in the different economic units and their quality, whether operational, investment or financing.